2021
DOI: 10.48138/cjo.934158
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Anti-obesity Effects of Melatonin and Niacin Supplements in Rat Models

Abstract: Son yıllarda dünyada obezitenin artması obezite ile mücadelede yeni stratejilerin geliştirilmesine yol açmıştır. Bu çalışmada, model organizma olarak ratlarda obezite ile mücadelede niasin ve melatonin takviyelerinin etkisinin araştırılması amaçlanmıştır. Ratlara 10 gün süreyle niasin ve melatonin takviyesi yapıldıktan sonra koşu bandı egzersizi yapıldı. Her grupta 10 günlük egzersiz sonunda kilo kaybı gözlendi. Bu çalışmada, koşu bandı egzersizi yapan ratlarda kontrol grubuna göre niasin takviyesinin kilo kay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Fukuwatari et al 69 reported that Nicotinic acid has no significant effect on bod weight and food intake in weaning rats. Previous studies also showed that Niacin supplementation decreased body weight in young rats 70 and enhances levels of NAD and expenditure of energy 71 . In regulation of energy metabolism and lipid metabolism NAD+/NADH plays a vital role 72 .…”
Section: Discussionmentioning
confidence: 83%
“…Fukuwatari et al 69 reported that Nicotinic acid has no significant effect on bod weight and food intake in weaning rats. Previous studies also showed that Niacin supplementation decreased body weight in young rats 70 and enhances levels of NAD and expenditure of energy 71 . In regulation of energy metabolism and lipid metabolism NAD+/NADH plays a vital role 72 .…”
Section: Discussionmentioning
confidence: 83%